VOCABULARY MASTERY AND READING COMPREHENSION OF IT EDUCATION DEPARTMENT STUDENTS - Ayu Rizki Septiana; Moh Hanafi (JURNAL EDUSCIENCE (JES), 2022)
This study is aimed at investigating the vocabulary mastery and the comprehension of passage of IT Education Department students. Vocabulary mastery is one of language component that is essential to be learned. Without any mastery on vocabulary, it will be very difficult to learn foreign language. Further, vocabulary is also important to comprehend a reading text or reading passage. The data in this research collected using two tests, vocabulary test and reading comprehension test. The result of vocabulary showed that the mean score of the class was 64.76 which was in the intermediate level. Further, the result of reading comprehension test showed that the mean score of the class was 74.28. The hypothesis testing was analyzed using Spearman correlational analysis. It showed that the significant value (0.299) was higher than the level of significance 0.05. Meanwhile, the coefficient of the correlation was 0.133. Thus, it can be concluded that there is no significant correlation between vocabulary mastery and the comprehension on reading passage of IT Education Department students. In the other words, vocabulary mastery does not contribute to IT Education Departments’ reading comprehension.